A woman’s pilgrimage to herself through the mother complex: A Jungian reading of selected works by Sylvia Plath - Pridgeon, Sarah Josie (University of the Free State, 2017)
Sylvia Plath’s work pioneers woman’s experience of herself, her identity, and the ample mental, psychic, emotional and physical phases of female development. Past scholarship has endeavoured to examine her work in terms of the father-daughter relationship, mostly within a Freudian ‘oedipal’ framework. Yet, to date no substantive study has sought to examine the inverse: the effects the mother-complex has had on her work and by implication, her identity and development as an individual, woman, poet and mother. To address this lacuna this study aims to examine the overlooked and highly significant effect the mother-complex has had on Plath’s construction of her identity in her work using anomalous Jungian theory, which posits that above all individuals seek ‘attainment of self’, that is, to unify the various dimensions of their psyche and become whole. I aim to analyse the rich transformative archetypes and symbolism indicative of this personal quest which was augured by her confrontation of the mother-complex. To ascertain the effects and examine such development, the apposite, selected texts for this study comprise the last phase of her works, her late poems (post-1961) and novel (The Bell Jar, 1963), which I have supplemented with her journals (The Unabridged Journals of Sylvia Plath, 2000) and the correspondence she had with her mother (Letters Home: Correspondence 1950-1963, 1975) to provide a thorough and all-inclusive investigation of this phenomenon. Plath’s confrontation of the rudimentary mother-complex and identity construction evident in these texts manifests in the consequential search for role models, the thematic dichotomies of life/death, creation/destruction and perfectionism characteristic of Plath’s work. The theoretical framework used to ascertain this hypothesis includes previously unapplied and befitting Jungian theory, Bowlby’s attachment theory as well as second-wave feminist theory. The foremost theoretical constructs, which highlight the effects the mother has on the daughter’s psyche and psychic growth, emphasises the interconnected dimensions of the psyche using Jung’s concepts of the mother-complex, shadow, persona, wise old woman and animus. Attachment theory demonstrates the preliminary nascence of this mother-complex. Alongside the analytical psychology and developmental models, aspects of second-wave feminism elucidate the impact that psycho-social factors have on identity development, and woman’s inherent ambivalence, as modelled by the mother and other women. This includes Betty Friedan’s ‘feminine mystique’ and how 1950s woman’s potentialities were restricted due to static professional and personal norms; Simone de Beauvoir’s concept of the ‘eternal feminine’ and woman as Other and Judith Butler’s ‘gender performativity’ which confines woman’s capabilities and influence to restrictive gender norms. Altogether this multi-faceted framework provides pertinent clarifications from a new angle for this hypothesis in connection with her mother Aurelia Plath, necessitating the impact of this on her life and work. This study, representative of one poet’s quest to cherchez la femme which follows the inherent need for ‘attainment of self’, can be extrapolated to fit into a broader framework that addresses the customary mother-daughter relationship interconnected with woman’s identity. The expansion of these two fundaments, relative to all women on a (personal and) collective level, is addressed in the last chapter of this study. This challenges the existing conceptualisations thereof to create a new narrative that is conducive to and necessitates woman’s multifarious needs, as an attempt to rewrite and recreate a unique trajectory for the development of the restrictive and prescriptive expectations established in woman’s consciousness, symptomatic of culture, as well as the affinities and aspirations within the collective unconscious.
Dissertation (M.A. (English))--University of the Free State, 2017
Keywords: Jungian psychology; Plath, Sylvia|; Feminism and literature; Psychoanalysis and literature